Characterization and photocatalysis of visible-light-driven Dy-doped ZnO nanoparticles synthesized by tartaric acid-assisted combustion method - Surisa Sa-nguanprang (2020)
© 2020 Elsevier B.V. ZnO samples containing different contents of Dy dopant were synthesized by a tartaric acid-assisted combustion method. The as-synthesized samples were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The samples with and without Dy dopant were specified as hexagonal wurtzite ZnO. The particle sizes of samples were decreased from 113 ± 31 nm for ZnO to 15 ± 3 nm for 5 wt% Dy-doped ZnO but the specific surface areas were increased from 3.58 m2·g−1 for ZnO to 28.35 m2·g−1 for 5 wt% Dy-doped ZnO. Both ZnO and 5 wt% Dy-doped ZnO samples revealed the strongest vibration peak of Zn–O stretching vibration E2H mode. Photocatalytic activities of the as-prepared ZnO and Dy-doped ZnO nanoparticles were investigated through photodegradation of methylene blue (MB) under UV visible light irradiation. The 5 wt% Dy-doped ZnO nanoparticles showed the highest photocatalytic activity for MB degradation of 97% within 75 min. The direct mass spectrometry specified that the MB solution was degraded by photocatalysis within 75 min.